PEMBAHARUAN HUKUM PERJANJIAN SPORTENTERTAINMENT BERBASIS NILAI KEADILAN (Studi Kasus Pada Petinju Profesional di Indonesia) - Hananto Prasetyo (Jurnal Pembaharuan Hukum, 2017)
This paper aims to examine the weakness that exist in the sportentertainment agreement between professional boxers and current managers. This study is included in the sociological juridicial study due to existence of field activities to find out the real situation in the field. The conceptual framework begins with the emergence of a lack fair sense of the boxer in his profession as an athlete. Primary data source from the interview result plunged into the field with the responses of professional athletes, while the secondary data sources are references related to the title, such as legislation relating to the agreement as well as bibliographic references. While data analysis using content analysis. The results indicate there is still much execution of agreement between professional athletes and managers who harmed the athlete due to lack of understanding of the agreement law